Cu nanoclusters in ion exchanged soda-lime glass: Study of SPR and nonlinear optical behavior for photonics. (June 2019) - Kumar, Promod; Mathpal, Mohan Chandra; Hamad, Syed; Rao, Soma Venugopal; Neethling, J.H.; van Vuuren, A. Janse; Njoroge, E.G.; Kroon, R.E.; Roos, W.D.; Swart, H.C.
Graphical abstract: Schematic diagram depicting plasmonic behavior of Cu NCs embedded in glass matrix. Highlights: The soda-lime glasses were successfully doped with Cu nanoclusters in the ion-exchange process. The similar size of the nanoclusters was estimated from the UV-Vis and TEM results. Z-scan technique was used to study the nonlinear optical properties. These plasmonic glasses may be useful in optical limiting and contrast enhancement. Abstract: Nanomaterials with large optical nonlinearities have received considerable attention in the field of modern science and nanotechnology. In this paper, we have studied nonlinear optical and surface plasmon resonance properties and behavior of Cu nanoclusters formed in ion exchanged soda-lime glass. The soda-lime glasses were successfully doped with Cu nanoclusters in the ion-exchange process. The size of the clusters estimated from the optical absorption spectroscopy results closely matched with those obtained from the transmission electron microscopy data. The results revealed that spherical shaped Cu nanoclusters were homogeneously distributed in the glass matrix and the size of the Cu nanoclusters varied from 4 to 10 nm. The structure and chemical state were further analyzed by X-ray diffraction and X-ray photoelectron spectroscopy. The nonlinear optical behavior of the materials was analyzed using femtosecond Z-scan technique. The nonlinear refraction index γ, nonlinear absorption coefficient β and the third-order nonlinear optical susceptibility χ (3) were estimated to be −1.72 × 10 −17 m 2 /W, 9.96 × 10 −11 m/W, and 0.56 × 10 −11 esu, respectively, which shows possible application in the field of photonics.